2009
DOI: 10.1111/j.1445-6664.2008.00320.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the differential response of weeds to soil solarization by two methods

Abstract: The efficacy of solarization in weed control under field conditions of the United Arab Emirates was evaluated by two methods: on-farm weed assessment and a seed germination test. In the on-farm weed assessment method, the weed frequency, density, and dry weight were compared in the solarized and non-solarized plots that were cultivated with cabbage. Prior to solarization, the soil was artificially infested with the seeds of 10 weeds. Generally, the densities of seven species and dry weights of five species wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
2
2
0
1
Order By: Relevance
“…The increase in biological and grain yield of sesame by extending the period of soil solarization was due to efficient weed control that reduced weed crop competition and increased growth and yield contributing traits of sesame. Our results are in the agreements with EL-Keblawy and Al-Hamadi (2009) and McGovern et al (2013), who reported an increase in biological yield and seed yield in soybean by prolonging the soil solarization duration.…”
Section: Effect Of Thermal Weed Control Treatments On Sesame Yieldsupporting
confidence: 93%
“…The increase in biological and grain yield of sesame by extending the period of soil solarization was due to efficient weed control that reduced weed crop competition and increased growth and yield contributing traits of sesame. Our results are in the agreements with EL-Keblawy and Al-Hamadi (2009) and McGovern et al (2013), who reported an increase in biological yield and seed yield in soybean by prolonging the soil solarization duration.…”
Section: Effect Of Thermal Weed Control Treatments On Sesame Yieldsupporting
confidence: 93%
“…Furthermore, certain legumes such as Mediterranean sweet clover (Melilotus sulcatus L.) and Medicago spp.(L.) are completely resistant to solarization due to their thick seed coat (Candido et al 2011, El-Keblawy and Al-Hamadi 2009, Powles et al 1988, Rubin and Benjamin 1984. Similar trends were observed in this study, where redstem filaree is not affected by solarization, but little mallow is affected after long exposure times even at lower temperatures of 45°C.…”
Section: Application To Field Conditionssupporting
confidence: 84%
“…For example, nutsedge tuber mortality will not occur until exposed to temperatures of 50°C or higher (Webster 2003). Also, many hard-seeded weeds with thick seed coats are difficult to control with solarization requiring longer solarization periods to achieve mortality (Egley 1990, El-Keblawy and Al-Hamadi 2009, Rubin and Benjamin 1984.…”
Section: Biosolarization Of Sudangrassmentioning
confidence: 99%
“…In the scientific literature, use of both clear and black tarps is often referred to as ‘solarization’, but the use of black tarps is often distinguished as ‘occultation’ within the farming literature. Most solarization research has employed clear tarps on bare soil and while weed control has been a focus of some studies, the primary goal has been pathogen control (Horowitz et al ., 1983; Standifer et al ., 1984; Stapleton and DeVay, 1986; Stapleton, 2000; El-Keblawy and Al-Hamadi, 2009). The efficacy of solarization as a weed management technique using clear tarps is dependent on the temperatures achieved, moisture and the weed species present.…”
Section: Introductionmentioning
confidence: 99%